Design and modeling of integrated octagonal shape inductor with substrate silicon in a buck converter - Abdelhadi NAMOUNE; Rachid TALEB; Noureddine MANSOUR; Abdelkader BELBOULA (IAES Indonesian Section, 2019)
The paper discusses the design and modeling of an integrate octagonal shaped inductor with silicon substrate. A validated equivalent electrical model of the integrated octagonal shaped spiral inductor is developed. The model is used to analyze and evaluate the quality factor and the inductance of the inductor structure proposed under different physical parameters setting. These include the number of turns, spacing between turns and the inner diameter. The simulation results show that an appropriate selection of physic a parameters can achieve an enhanced quality factor and improved inductance. PSIM simulator is used for the implementation of the integrated inductor in a micro buck converter. The simulation results demonstrate that our proposals are very promising approaches for the monolithic integration of DC-DC converters.